Common biological phenotypes characterize the acquisition of platinum-resistance in epithelial ovarian cancer cells - Maura Sonego (Nature Portfolio, 2017)
Abstract Standard of care for Epithelial Ovarian Cancer (EOC) patients relies on platinum-based therapy. However, acquired resistance to platinum occurs frequently and predicts poor prognosis. To understand the mechanisms underlying acquired platinum-resistance, we have generated and characterized three platinum-resistant isogenic EOC cell lines. Resistant cells showed 3-to 5- folds increase in platinum IC50. Cross-resistance to other chemotherapeutic agents commonly used in the treatment of EOC patients was variable and dependent on the cell line utilized. Gene expression profiling (GEP) of coding and non-coding RNAs failed to identify a common signature that could collectively explain the mechanism of resistance. However, we observed that all resistant cell lines displayed a decreased level of DNA platination and a faster repair of damaged DNA. Furthermore, all platinum resistant cell lines displayed a change in their morphology and a higher ability to grown on mesothelium. Overall, we have established and characterized three new models of platinum-resistant EOC cell lines that could be exploited to further dissect the molecular mechanisms underlying acquired resistance to platinum. Our work also suggests that GEP studies alone, at least when performed under basal culture condition, do not represent the optimal way to identify molecular alterations linked to DNA repair pathway defects.